FAUNA IKAN EKOSISTEM HUTAN RAWA DISUMATERA SELATAN [Fish Fauna of Swampforest Ecosystem in South Sumatera] - Syarifah Nurdawati; Dadjek Prasetyo (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2007)
Research on fish fauna in some types of swamp forest was done during two seasons that are rainy season and dry season as a mean to describe fish species living in Cala Lake ecosystem. This research was done by specifying some stations that are Kutung River (I), Dua Besar River (II), Cala Lake (III), and Candi Floodplain (IV). Gathering of fish species by taking fisherman catches with not selective gear (empang, kilung and corong). At this research, it was found 75 fish species consisted of seven orders, 20 families, 45 genera, and 75 species; where 53 species were found at station I, 51 species at station II, 53 species at station HI, and 41 species at station IV. As many as 58 species fish seed found at swamp forest to find food (feeding ground), 31 fish species is doing spawn (spawning ground), and 14 fish larvae stay -in the swamp forest indicating a nursery ground.